Tingkat Pengetahuan Nelayan Tentang Keselamatan Pelayaran - Ike Nurhayati Efendi; Dedeh Suryani; Andi hendrawan (Sekolah Tinggi Maritim Yogyakarta, 2022)
Shipping safety is mandatory in terms of activities at sea. Recognizing the importance of safety in shipping both before sailing and during sailing, this is because safety is the main goal in transporting and in working, the attention of all parties is always safety as the main goal. This study aims to assess the level of knowledge of fishermen about shipping safety, whether they work as fish catchers or in the field of sea transportation. The sample used is 50 fishermen who are in the city of Cilacap. The research method used is quantitative by giving a questionnaire and then assessing the level of knowledge. The results showed that the category was sufficient and good, namely 20 people or 40% and at least in the less category, namely 10 people or 20%, this shows that the average level of knowledge of fishermen about shipping safety. To increase knowledge, socialization and training are needed. Increasing knowledge can be done by socialization through mass media and training carried out regularly by the government and other non-governmental organizations.